A Study on Design Variables for Increasing the Breaking Strength of Synthetic Fiber Chain - Kyeongsoo Kim; Seonjin Kim; Hyunwoo Cho; Dokyoun Kim; Yongjun Kang; Taewan Kim (한국해양공학회지, 2023)
In this study, a fiber chain was developed to replace a steel chain using high-modulus polyethylene DM20. The pick count, wrapping count, and inner length were selected as the main design variables of the fiber chain and were analyzed to increase the breaking strength. Orthogonal array experiments were conducted, and the results were analyzed with respect to the breaking strength. The analysis revealed that the pick count and wrapping count had meaningful effects at significance levels within 5%. The main effect analysis revealed that a smaller pick count, larger wrapping count, and longer inner length caused the breaking strength to increase. With the wrapping count fixed at 1, a pick count less than -0.65, and an inner length greater than 0.38, the breaking strength was calculated to be greater than 300 kN. These results are expected be important factors in the derivation of an optimal combination of design variables to attain a fiber chain with a targeted strength.